Building information modelling creating customized wall family liblary using revit 2014 - Muhaiza , Awang (2015)
BIM applications in construction projects bring many benefits to construction players such as improving communication between construction players and facilitating faster design decision. Moreover, one of the BIM features is ease of use related to its tools; hence, the use of BIM can reduce time spent in design as well as decrease cost and duration of construction Revit architecture become one of the popular BIM tools that has widely used in construction industry.Together with drafting building components in 2D and 3D, it also allows 4D BIM which facilitates for architects and engineers. Wall is one of the elements in Revit. Wall is a structure that defines an area, carries a load, or provides shelter or security. The barrier which always happen in revit is the limitation of wall type in standard Revit family library .Moreover, type of wall that has been provide is not fulfil the specification for construction industry. To cater the issue, this study has been conducted to identify and develop customized wall family library_By using edit type method, new type of wall were created to be used by the BIM user. This semi structure interview was conducted in order to achieve the objectives. The respondents consisted of architects, contractors, developers, consultants and quantity surveyors. The processes of developing new customized wall are using Revit 2014 software. In conclusion, the limitation in standard wall family library in Revit has been identified and discussed. From this research new customized wall family library has been created by using edit type method to catcher the issue of limitation of wall type in standard Revit. This solution can help engineer/architect to develop their own customized wall which is fulfilling the specification from industry.